(untitled) (Swiss Medical Weekly, 2015)
OBJECTIVE: The aim of this study was to develop a generic instrument for the use of patients, named the Knee Osteoarthrtis Patient Education Questionnaire (KOPEQ), to assess the validity of a preoperative educational intervention and to make a preliminary test of its psychometric properties. METHODS: A patient-reported outcome instrument was designed, using the conceptual framework of Wilson and Cleary as a methodological guide. Likert items with a five-point scale were chosen for the scoring option. The feasibility and interpretability of administering the KOPEQ was tested through conducting interviews with targeted patients. Items of the KOPEQ were linked to the International Classification of Functioning, Disability and Health (ICF). Psychometric testing contained internal consistency for reliability, and factor analysis for validity properties. RESULTS: A final list of 16 items was derived and linked to the ICF. Targeted patients confirmed in interviews, that all 16 questions were highly understandable and that the length of the questionnaire was feasible and acceptable. There was a good internal consistency for the 16-item KOPEQ with a Cronbach’s alpha of 0.83 (95% confidence interval 0.71–0.94). Sixty-one percent of the variance was explained by a four-factor model and the factors were named “didactics”, “addressability”, “empowerment” and “theory”. Results of a factor analysis provided a loading of the separate items between 0.469 and 0.958. CONCLUSIONS: The KOPEQ can help to provide health professionals with reliable feedback on how patients assessed the applied patient education intervention. Interviews with patients and a factor analysis revealed new and important insight. Key words: patient edication; questionnaire; knee; osteoarthritis